BS EN ISO 6647-1. Rice. Determination of amylose content. Part 1. Reference method: Spectrophotometric method with a defatting procedure by methanol and with calibration solutions of potato amylose and waxy rice amylopectin (28th October 2019) - British Standards Institution,
No abstract available